Relationship Analysis of Capital Structure and Profitability Ratio in Trade Sector Companies in Indonesia - Ranila Suciati; Marlina Marlina; Zackharia Rialmi; Heni Nastiti (DINASTI RESEARCH, 2021)
A composition or a structure of liabilities is the definition of the capital structure of a company. The purpose of the study is to analyze the structure of capital and the performance of finance during the years 2015 to 2018 (4 years) in the enterprise sector is national Trade in Indonesia. The research sample was processed from the annual report data Trade sector companies in Indonesia that are listed on the Indonesia Stock Exchange, this is in accordance with the objectives of this study. The method of analysis in this study uses panel data regression. The relationship between capital structure and profitability ratios will be revealed from this study. Variables independently that structure capital will be in proxy with a debt to equity ratio (DER), debt to asset ratio (DAR), and long-term debt ratio (LTDR). And for variable dependent is the performance of finance will be in proxy with Gross Profit Margin (GPM), Net Profit Margin (NPM), and Return on Capital Employed (ROCE). Research on the company's sector of Commerce in Indonesia resulted in a relationship that significant between variables independent manner together against variable dependent.